2011
DOI: 10.1186/1471-2105-12-47
|View full text |Cite
|
Sign up to set email alerts
|

Accurate statistics for local sequence alignment with position-dependent scoring by rare-event sampling

Abstract: BackgroundMolecular database search tools need statistical models to assess the significance for the resulting hits. In the classical approach one asks the question how probable a certain score is observed by pure chance. Asymptotic theories for such questions are available for two random i.i.d. sequences. Some effort had been made to include effects of finite sequence lengths and to account for specific compositions of the sequences. In many applications, such as a large-scale database homology search for tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Third, it has been shown that the results obtained with Rare Event Sampling with one and two random sequences are not identical but show serious differences 56. As we pointed out, the query sequence is not random and it makes sense to keep it fixed.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Third, it has been shown that the results obtained with Rare Event Sampling with one and two random sequences are not identical but show serious differences 56. As we pointed out, the query sequence is not random and it makes sense to keep it fixed.…”
Section: Discussionmentioning
confidence: 92%
“…We identified the Gumbel distribution with Gaussian correction as best approximation for the empirical alignment score distributions obtained with Rare Event Sampling . This combination has been suggested before for local alignments of protein sequences of shorter length 55,56. The sequences generated with PhAST are not of biological origin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations